(untitled) (Web of Teachers: Inderscience Research, 2025)
Islamic insurance, or Takaful, has gained significant prominence in the global financial markets, providing a Sharia-compliant alternative to conventional insurance. Its legal nature is founded on the principles of mutual cooperation, shared risk, and ethical investment, which distinguish it from profit-driven models typically seen in Western insurance systems. The paper aims to explore the legal nature of Islamic insurance, analyzing the regulatory and legal challenges it faces in Germany, the UK, and Uzbekistan, three countries with diverse legal traditions. Through a comparative legal approach, the paper examines how Islamic insurance is integrated within these jurisdictions, addressing issues such as Sharia compliance, regulatory oversight, and the advantages and disadvantages of implementing Takaful. The findings demonstrate that while the implementation of Islamic insurance offers numerous benefits, including inclusivity and ethical financial management, it also faces challenges, particularly in the areas of legal harmonization and market acceptance.